Frações contínuas : uma aplicação em criptografia RSA - Silva, Márcio Alexandre dos Santos (2019)
This dissertation presents a study on the expansion of real numbers in the form of simple continuous fractions and an application of this theory to the RSA cryptography system. In the first chapter the definitions, properties and reduced of these fractions are discussed. They are further explained as the best approximations of a number for a given denominator. Once this preliminary study is established, the second chapter presents the attack on RSA cryptography developed in 1990 by Wiener. Thus, this paper aims to address this attack by studying the simple continuous fractions.